Outcomes following left ventricular assist device exchange. Issue 3 (16th January 2020) - Imamura, Teruhiko; Narang, Nikhil; Rodgers, Daniel; Nguyen, Ann; Ota, Takeyoshi; Song, Tae; Kim, Gene; Raikhelkar, Jayant; Jeevanandam, Valluvan; Sayer, Gabriel; Uriel, Nir
Abstract: Introduction: Left ventricular assist device (LVAD) exchange has been historically associated with a significant risk of morbidity and mortality. It is unknown, however, whether these outcomes have improved. We aimed to compare clinical outcomes following LVAD exchange to those following initial LVAD implant in a contemporary patient cohort. Methods: A total of 115 LVAD patients were enrolled between 2014 and 2017 and followed for 1 year. Of these, 15 patients (54.5 ± 13.3 years old, 87% male) underwent LVAD exchange at 277 (IQR 191‐597) days following LVAD implantation and 100 patients (57.5 ± 12.3 years old, 76% male) did not undergo an LVAD exchange (non‐exchange group). Results: One‐year survival rate following LVAD exchange tended to be higher than the non‐exchange patients (93% vs 76%, P = .15). Readmission rates for each comorbidity did not significantly differ between the two groups ( P  > .05 for all) except for the higher rate of pump thrombosis in the LVAD exchange group ( P  < .05). Discussion: LVAD exchange cohorts seem to have comparable clinical outcome with the non‐exchange cohorts. Conclusion: LVAD exchange might be an increasingly appropriate therapeutic option for the management of pump thrombosis, although careful monitoring for recurrent pump thrombosis is required.